The Social, Cultural and Historical Context of Aboriginal and Torres Strait Islander Australians - Dudgeon, P.; Wright, M.; Paradies, Y.; Garvey, Darren; Walker, I. (Commonwealth of Australia, 2010)
To understand the contemporary life of Indigenous Australians, a historical and cultural background is essential. This chapter sets the context for further discussions about Aboriginal and Torres Strait Islander people and issues related to their social and emotional wellbeing and mental health. The history of colonisation is addressed, the subsequent devastation of Indigenous Australians, and their resilience and struggle to claim equality and cultural recognition, and to shape the present. Indigenous Australia is made up of two cultural groups who have shared the same struggle, yet often when using the term Indigenous, a Torres Strait Islander history is absent. In this chapter both cultures are equally presented. Brief overviews are given of pre-contact times, colonisation, resistance and adaptation, shifting government policies, and the struggle for recognition. Indigenous identity and meanings of belonging in country, community and family are also briefly covered. Contemporary issues confronting Indigenous people are included, with particular attention to racism.